High-performance all-organic aqueous batteries based on a poly(imide) anode and poly(catechol) cathode. Issue 1 (16th December 2020) - Patil, Nagaraj; Mavrandonakis, Andreas; Jérôme, Christine; Detrembleur, Christophe; Casado, Nerea; Mecerreyes, David; Palma, Jesus; Marcilla, Rebeca
Abstract : All-organic aqueous batteries based on universal poly(imide) anodes and poly(catechol) cathodes with tunable cell voltage are reported by exploiting different charge carriers (Li +, Zn 2+, Al 3+, and Li + /H + ). A full-cell achieves the highest energy/power density of 80.6 W h kg −1 /348 kW kg −1 in Li + /H + . Abstract : Aqueous all-polymer batteries (AqPBs) are foreseen as promising solutions for safe, sustainable, and high-performance energy storage applications. Nevertheless, their development is still challenging as it demands precise optimization of both electrodes and the electrolyte composition to be able to sustain a stable redox activity, while delivering an optimal voltage output. Herein, we report AqPBs based on a poly(imide) (PI) anode and poly(catechol) (PC) cathode that exhibit tunable cell voltage depending on the salt used in the aqueous electrolyte, i.e., 0.58, 0.74, 0.89, and 0.95 V, respectively, when Li +, Zn 2+, Al 3+, and Li + /H + were utilized as charge carriers. The PI–PC full-cell delivers the best rate performance (a sub-second charge/discharge) and cycling stability (80% capacity retention over 1000 cycles at 5 A g −1 ) in Li + . Furthermore, a maximum energy/power density of 80.6 W h kganode+cathode −1 /348 kW kganode+cathode −1 is achieved in Li + /H +, superior to most of the previously reported AqPBs.